1999
DOI: 10.1080/01140671.1999.9514075
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in New Zealand populations of the plant pathogenSclerotinia sclerotiorum

Abstract: Genetic variation of the fungal plant pathogen Sclerotinia sclerotiorum (Lib.) de Bary was examined using DNA fingerprinting. Seventyfive isolates of S. sclerotiorum were collected from four populations in the South Island of New Zealand. DNA fingerprints were generated for each isolate by Southern blotting using a cloned repetitive sequence, pLK44.20, as a probe. The 47 different fingerprints produced revealed a high level of variation both within and between populations. Comparison of fingerprint similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 13 publications
4
37
0
Order By: Relevance
“…Variability among the isolates has already been reported by Carpenter et al (1999). All isolates were darkly pigmented.…”
Section: Discussionsupporting
confidence: 68%
“…Variability among the isolates has already been reported by Carpenter et al (1999). All isolates were darkly pigmented.…”
Section: Discussionsupporting
confidence: 68%
“…Prior researches on S. sclerotiorum population structure, in areas where canola, sunflower, cabbage, and other crops are grown, have shown that this pathogen populations are mainly clonal (Kohli et al, 1992(Kohli et al, , 1995Anderson and Kohn, 1995;Cubeta et al, 1997;Kohli and Kohn, 1998;Carpenter et al, 1999;Hambleton et al, 2002), even though some recombination has been detected (Cubeta et al, 1997;Carbone and Kohn, 2001a), being more evident in subtropical populations than in temperate ones (Carbone et al 1999;Carbone and Kohn, 2001b;Atallah et al, 2004;Sexton and Howlett, 2004;Sexton et al, 2006;Mert-Türk et al, 2007;Gomes et al, 2011).…”
Section: Recombination Vs Clonal Reproductionmentioning
confidence: 99%
“…Several works have deployed MCG typing in population studies of both S. sclerotiorum and Sclerotinia minor (Kohli et al, 1992(Kohli et al, , 1995Cubeta et al, 1997;Carpenter et al, 1999;Carbone and Kohn, 2001b;Hambleton et al, 2002;Phillips et al, 2002;Durman et al, 2003;Hollowell et al, 2003;Kull et al, 2004;Atallah et al, 2004;Sexton and Howlett, 2004). Individual isolates are classified into clonal lineages by the use of two or more independent markers such as MCGs, DNA fingerprinting, or microsatellite markers (Kohn et al, 1991;Carbone et al, 1999;Sirjusingh and Khon, 2001;Hambleton et al, 2002;Auclair et al, 2004).…”
Section: Recombination Vs Clonal Reproductionmentioning
confidence: 99%
“…Oilseed rape is a new crop to this area and the high level of polymorphism may reflect the movement of S. sclerotiorum ascospores onto rapeseed crop from several wild host plants. 28 …”
Section: Genetic Diversity Among the Sclerotinia Sclerotiorum Isolatesmentioning
confidence: 99%